A mediação pedagógica no desenvolvimento de uma sequência de ensino investigativa que articula conhecimentos astronômicos e físicos - Silva, Rodolfo Sant Ana (2019)
In this dissertation we present a research resulting from the development and implementation of an Inquiry-Based Teaching Sequence (IBTS) that articulates physics and astronomical knowledge. The objective of IBTS is to promote the practice of astronomical observation, with and without instruments, while providing the development of physical knowledge about refraction and reflection phenomena through the study of telescopes. The objective of the research is to analyze the pedagogical mediation in the development of IBTS with high school students. The intervention was implemented in four classes of the second grade of a high school of a school located in the country of Serra of Espírito Santo state network, being 63 boys and 65 girls, totaling 138 students aged 15 to 18 years old, between June and August of 2018. The classes were recorded in audio and video. The classes were transcribed so that through the discursive interactions established in the classroom it was possible to analyze the mediation established during the IBTS being careful with consistensy with inquiry in science teaching assumptions. For the dissertation we brought the analysis of two classes, one configured as investigative and the other as non- investigative, which allowed us to rethink the interactions established in these classes. These analyzes indicate that the self-assessment of teaching practice can contribute positively to the understanding of the elements that occurred throughout the class and, consequently, a better understanding of the investigative perspective, allowing us to rethink the actions and contextualization for the next interventions. Assuming research teaching as a pedagogical stance requires a change in the way of interacting and establishing mediations in the classroom, and this movement is an important process for appropriating the approach.